Identifying Contextual Factors of Employee Satisfaction of Performance Management at a Thai State Enterprise - Saratun, Molraudee; Rungruang, Parisa (UI Scholars Hub, 2013)
Although there has been an increase in Performance Management (PM) literature over the years arguing that PM perceptions are likely to be a function of PM process components and contextual factors, the actual relationship between the contextual factors and employee satisfaction of PM remains little explored. Extending previous research, this study examines relationships between contextual factors and employees’ PM satisfaction. Derived from the literature, these contextual factors are motivation and empowerment of employees, role conflict, role ambiguity, perceived organisational support, procedural justice and distributive justice. Seven directional hypotheses are tested accordingly through a series of regression analyses. This article finds that these contextual factors, with the exception of role conflict, are directly predictive of enhanced employees’ PM satisfaction at the Thai state enterprise.